Scale-dependent spatial match between fruits and fruit-eating birds during the breeding season in Yungas Andean forests - Blendinger, Pedro Gerardo (2015)
The multi-scale spatial match between bird and food abundances is a main driver of the structure of fruit-eating bird assemblages. We explored how the activity of fruit-eating birds was influenced by the abundance of fruits at the local and landscape scales in Andean mountain forests during the breeding season, when most birds forage close to their nest. We measured: (1) the spatial scale of variation in the abundance of fruits, (2) the spatial scale of variation in the activity of fruit-eating birds, and (3) the spatial match between both variables. The sampling design consisted of eleven 1.2-ha sites, each subdivided into 30 cells of 20 × 20 m, where we sampled fruits and fruit-eating birds. We found that fruit consumption, and to a lesser extent bird abundance, were associated with local spatial variation in abundance of selected fruit species. However, fruit-eating birds did not modify their spatial distribution in the landscape following changes in availability of these fruits. Our study shows that fruit-eating birds detect local spatial variation in fruit availability in their home breeding ranges, and exploit patches with large clusters of selected fruits. However, it may be unprofitable for breeding birds to stray too far from their nests to exploit fruit-rich patches, accounting for the absence of fruit tracking at larger spatial scales.